PENGARUH LINGKUNGAN BELAJAR DAN KOMPETENSI PROFESIONAL GURU TERHADAP PRESTASI BELAJAR SISWA SMA N 1 JEKULO KUDUS - Rustiana, Ade; Chalifah, Noor (Fakultas Ekonomi, Universitas Negeri Semarang, 2012)
Learning environment and teachers’ professional competence are factors which can affect students’ achievement. The objective of the study was to determine the influence of learning environment and teachers’ professional competence toward students’ achievement either partially or simultaneously. The populations were 133 students and the samples were 100 students. Then, data were collected by questionnaires and documentation. The calculation of multiple regression resulted the equation of Y = 60.866 + 0.114 X1 + 0.048 X2. The coefficient of determination simultaneously; learning environment and teachers’ professional competence toward students’ achievement was 53.3%, the coefficient of determination partially; learning environment toward students’ achievement was 26.3%, and teachers’ professional competence toward students’ achievement was 16.9%. It was concluded that there was significant influence of learning environment toward students’ achievement, there was no significant influence of the teachers’ professional competence toward students’ achievement, and there was significant influence of learning environment and teachers’ professional competence toward students’ achievement.